Middle and distal bile duct carcinoma, retrospective analysis & short-term and long-term outcomes of surgical therapy - Skalický, P; Tesaříková, J; Gregořík, M; Knápková, K; Švébišová, H; Kurfúrstová, D; Klos, D; Loveček, M (Rozhledy v chirurgii, 2022)
INTRODUCTION: The prognosis of extrahepatic cholangiocarcinoma is dismal and the only way to achieve long-term survival is surgical resection. While pancreatoduodenectomy (PD) is the standard procedure for distal cholangiocarcinoma (distal bile duct cancer; DBDC), bile duct segmental resection (BDR) can be used as an alternative approach for middle bile duct cholangiocarcinoma (middle bile duct cancer; MBDC). The aim of the study was to calculate the short-term and long-term outcomes of curative-intent surgery in distal bile duct cholangiocarcinoma patients. METHODS: A retrospective cohort study of consecutive patients treated for MBDC and DBDC with PD or BDR between 1/2009-12/2019. The patients were divided according to the type of surgical resection (PD and BDR group). Demographic, clinicopathological and histopathological data and overall survival (OS) were evaluated in both groups. OS was estimated using the Kaplan-Meier analysis. RESULTS: The study comprised a total of 62 patients - 45 patients (72.6%) in the PD group and 17 (27.4%) in the BDR group. Patients undergoing BDR were significantly older than those receiving PD (p=0.048). Men predominated in the PD group (N=34/45; 75.6%) while more women were included in the BDR group (N=10/17; 58.8%). Median age was higher in the BDR group (p=0.048). Serious morbidity (Clavien-Dindo III-V) (33.3% vs 11.8%), 30-day and 90-day mortality (4.4% vs 0.0% and 8.9% vs 5.9%, respectively) predominated in the PD group although the differences were not statistically significant, as well as a longer hospital stay (16.0 days vs 11.0 days; p=0.002). Pathological assessments revealed comparable numbers of positive lymph nodes in both groups, but a significantly higher number of total resected lymph nodes in the PD group (p.
Keywords: Prognosis; distal bile duct cancer; žlučové cesty extrahepatické; nádory žlučových cest; Male; Retrospective Studies; žlučové cesty intrahepatální; lidé; Humans; retrospektivní studie; cholangiokarcinom; Bile Duct Neoplasms; bile duct resection; Bile Ducts, Intrahepatic; mužské pohlaví; ženské pohlaví; middle bile duct cancer; Female; Cholangiocarcinoma; prognóza; pancreatoduodenectomy; Bile Ducts, Extrahepatic